Utilization of Booklet Media in Providing Information Services for Students' Understanding of Career Choice - Mimi Suriatie; Ramadhanti Rizka; Oktamia Karuniaty Sangalang (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study is an experimental research using the